Circle Actions on Four Dimensional Almost Complex Manifolds With Discrete Fixed Point Sets - Jang, Donghoon (International mathematics research notices, 2024)
We establish a necessary and sufficient condition for pairs of integers to arise as the weights at the fixed points of an effective circle action on a compact almost complex 4-manifold with a discrete fixed point set. As an application, we provide a necessary and sufficient condition for a pair of integers to arise as the Chern numbers of such an action, answering negatively a question by Sabatini whether $c_{1}^{2}[M] ≤ 3 c_{2}[M]$ holds for any such manifold $M$. We achieve this by demonstrating that pairs of integers that arise as weights of a circle action also arise as weights of a restriction of a $\mathbb {T}^{2}$-action. Furthermore, we discuss applications to circle actions on complex/symplectic 4-manifolds and semi-free circle actions with discrete fixed point sets.